Efeito da endogamia na seleção genômica em populções simuladas de aves poedeiras - Nascimento, Guilherme Batista do [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The objective of this study was to evaluate the prediction accuracy of genomic breeding values for traits of different heritability in simulated populations with different inbreeding. Phenotypic and genotypic data were simulated based on the population structure of an experimental population of White Leghorn hens at Embrapa Suínos e Aves. The phenotypes and genotypes were simulated for the rate of total egg production (PTO) and egg weight to 32 weeks of age (PO) with heritability of 0.15 and 0.37, respectively. The historical population was simulated to generate linkage disequilibrium in the population. Three scenarios in recent populations were simulated for each trait: REC1, REC2 and REC3 to maximize inbreeding, minimize inbreeding and random mating, respectively. The animals were selected based on the largest breeding values along 10 generations. The genome of the birds was simulated with eight macro-chromosomes and 19 micro-chromosomes with 3.747 QTL randomly distributed and 49.978 SNPs markers evenly spaced along the 958 cM. Recombination, random drift and recurrent mutation were simulated in order to generate genetic variability. The linkage disequilibrium (LD), effective population (Ne) and genetic trends were calculated for all scenarios. Each recent population was divided in training and validation sets In order to predict the genomic breeding values. The training set included the genotypes and phenotypes of 960 animals, which had higher breeding values’ accuracy. The validation set had 1120 animals of the last generation of the recent population. The average inbreeding ranged from 0.06 ± 0.30 to 0.22 ± 0.12 for PTO and 0.05 ± 0.03 to 0.20 ± 0.12 for PO. The REC1 populations had higher inbreeding along generations compared, both for PTO and PO, compared to REC2 and REC 3, and consequently higher level of LD. The highest accuracy for PTO and PO were ...

O objetivo do presente trabalho foi avaliar a acurácia de predição dos valores genéticos genômicos para características de diferentes herdabilidades, em populações simuladas de aves com diferentes níveis de endogamia. Os dados fenotípicos e genotípicos foram simulados com base na estrutura populacional de uma população experimental de aves poedeiras. Foram simulados os fenótipos e os genótipos de aves para características de taxa de postura total de ovos (PTO) e peso dos ovos as 32 semanas de idade (PO), com herdabilidades de 0,15 e 0,37 respectivamente. Foi simulada uma população histórica a fim de gerar desequilíbrio de ligação na população e esta deu origem as populações recentes em que foram simulados três cenários populacionais, visando maximizar (REC1), minimizar (REC2) e aleatorizar (REC3) os acasalamentos endogâmicos. Ao longo de 10 gerações recentes, os animais foram selecionados com base nos maiores valores genéticos preditos (VGP), utilizando o BLUP (best linear unbiased prediction) tradicional. O genoma das aves foi simulado ao longo dos 958 Mb do genoma Gallus gallus 4.0 com 3.747 QTL (loci de caracteres quantitativos) aleatoriamente distribuídos e 49.978 marcadores SNP uniformemente distribuídos. A fim de alterar as frequências alélicas e gerar variabilidade genética ao longo das gerações, foram simulados eventos de deriva genética, taxa de recombinação e mutação recorrente. Para avaliar os efeitos da endogamia nas populações recentes, foram calculados os desequilíbrios de ligação (DL), o tamanho efetivo da população (Ne) e as tendências genéticas em todos os cenários de populações recentes em ambas as características simuladas. Para predizer os valores genéticos genômicos preditos (VGGP), as populações recentes foram subdivididas em populações de treinamento e validação. Nas subpopulações de treinamento, os 960 animais ...
Keywords: Ave poedeira; Genômica; Genoma; Endogamia; Genetica animal; Genomics